Rapid GC-MS method for screening seized drugs in forensic investigations: optimization and validation - Askar, Asma M.; Al Ali, Auhood Y.; Khalifa, Meera K.; Salem, Ali A.; Alkhuwaildi, Buthaina M.; Shah, Iltaf (Frontiers in Chemistry, 2025)
IndroductionThe escalating incidence of drug-related crimes requires rapid and reliable forensic methods for drug screening.MethodsThis study develops and optimizes a rapid Gas Chromatography-Mass Spectrometry (GC-MS) method that significantly reduces the total analysis time from 30 to 10 minutes, facilitating faster judicial processes and law enforcement responses. Enhanced by optimizing temperature programming and operational parameters, the method efficiently shortens the run time while ensuring the accuracy essential for forensic applications.ResultsThrough systematic validation, the method demonstrated a limit of detection improvement by at least 50% for key substances such as Cocaine and Heroin, achieving detection thresholds as low as 1 μg/mL for Cocaine compared to 2.5 μg/mL with conventional method. Additionally, the method exhibited excellent repeatability and reproducibility with relative standard deviations (RSDs) less than 0.25% for stable compounds under operational conditions. Applied to 20 real case samples from Dubai Police Forensic Labs, the rapid GC-MS method accurately identified diverse drug classes, including synthetic opioids and stimulants, with match quality scores consistently exceeding 90% across tested concentrations.ConclusionThe method effectively reduces forensic backlogs, facilitating faster and more reliable drug screening essential for judicial processes.